Prediksi Jumlah Tamu Hotel di Provinsi NTB dengan Metode Monte Carlo - Yesika Syalomi Pasaribu (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
West Nusa Tenggara (NTB) Province is a leading tourism destination in Indonesia, which requires predictions of the number of hotel guests for effective planning and resource management. This research aims to predict the number of hotel guests in NTB in 2025 using the Monte Carlo method, which is able to handle data variability and uncertainty. The data used is the number of guests from 1 to 5 star hotels during 2022. The simulation results show fluctuations in the number of guests throughout 2025 with the highest peak in December, especially in 3 star and 4 star hotels. The Monte Carlo method has proven to be effective in providing accurate predictions. accurate and reliable. The implication of this research is that stakeholders in the NTB hotel and tourism sector can use the results of these predictions for better strategic planning and decision making. This research is limited to data for 2022, so it is recommended that further research use data with a longer time span and consider external factors that influence the number of hotel guests. Combinations of other prediction methods can also be explored to improve the accuracy and reliability of predictions.